2020
DOI: 10.1136/bmjopen-2019-036093
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a randomised-controlled study on emotion regulation training for adolescents with major depression: the KONNI study

Abstract: IntroductionMajor depression (MD) often has its onset during adolescence and is associated with significant morbidity and mortality. One important factor for the development and maintenance of adolescent MD are disturbances in emotion regulation and the underlying neural processes. Cognitive reappraisal (CR) is a particular adaptive emotion regulation strategy. Previously, it has been shown in healthy adults that a task-based training in CR is efficient to reduce negative affect, and that these effects transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Considering the absent differential effect of the training on our primary outcome measures, it should be noted that our sample size was derived from the assumption of a large effect on rumination (Greimel, Feldmann, et al, 2020; Siegle et al, 2014), so it may well be possible that the absence of significance is due to our sample size being not sufficiently large to detect smaller effects. Indeed, a study researching add-on ER training in addition to CBT on over 400 participants (Berking et al, 2013) similarly only found a small effect of the training on depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the absent differential effect of the training on our primary outcome measures, it should be noted that our sample size was derived from the assumption of a large effect on rumination (Greimel, Feldmann, et al, 2020; Siegle et al, 2014), so it may well be possible that the absence of significance is due to our sample size being not sufficiently large to detect smaller effects. Indeed, a study researching add-on ER training in addition to CBT on over 400 participants (Berking et al, 2013) similarly only found a small effect of the training on depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This study was preregistered on Clinical Trials (identifier: NCT03957850) and a study protocol was previously published in BMJ Open (Greimel, Feldmann, et al, 2020). All study procedures were approved by the local ethics committee of the Medical Faculty of the Ludwig-Maximilians-University (LMU) Munich and were performed in accordance with the latest version of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, maladaptive emotion regulations are important factors for development and maintenance of depression (Sloan et al, 2017). However, adaptive strategies, such as reappraisal and acceptance, are useful to alleviate depressive symptoms (Greimel et al, 2020; Sloan et al, 2017). Our preliminary evidence supports that notion of careful selection of MDD subtypes with problems of emotion regulation for specific treatments in patients with MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive behavior therapy has been recommended by NICE guidelines for the treatment of MD and AN in adolescence [78,79] and is well suited to promote adaptive ER strategies and direct focus away from maladaptive coping points. As an add-on to CBT, ER training has shown beneficial effects in adults with MD [80] and similar approaches for ER training in adolescent MD are being developed [81].…”
Section: Discussionmentioning
confidence: 99%